2022
DOI: 10.1108/ijchm-03-2022-0340
|View full text |Cite
|
Sign up to set email alerts
|

The greater the incentives, the better the effect? Interactive moderating effects on the relationship between green motivation and green creativity

Abstract: Purpose This study aims to address the gap in hospitality and tourism (H&T) research concerning green creativity (GC) and seeks to identify the ways in which the interaction between spiritual incentives (SI) and material incentives (MI) affects the relationships among green intrinsic motivation (GIM), green extrinsic motivation (GEM) and GC. Design/methodology/approach In accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, this paper examines studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, this study's findings show that both GIs and AoC have positive and significant effects in developing GE. These findings are, also, consistent with those of previous studies (Marshall and Samal, 2006;Pacheco et al, 2010;Nandanwar et al, 2010;Tuszynski and Stansel, 2018;Mrkajic et al, 2019;Liu and Liu, 2023;Arsawan et al, 2023;AlQershi et al, 2023). These findings demonstrate that the Saudi Arabian taxation system favors green business activities and that the Saudi Arabian Government's offers favorable incentives and the presence of management that values the environment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, this study's findings show that both GIs and AoC have positive and significant effects in developing GE. These findings are, also, consistent with those of previous studies (Marshall and Samal, 2006;Pacheco et al, 2010;Nandanwar et al, 2010;Tuszynski and Stansel, 2018;Mrkajic et al, 2019;Liu and Liu, 2023;Arsawan et al, 2023;AlQershi et al, 2023). These findings demonstrate that the Saudi Arabian taxation system favors green business activities and that the Saudi Arabian Government's offers favorable incentives and the presence of management that values the environment.…”
Section: Discussionsupporting
confidence: 91%
“…, 2010; Tuszynski and Stansel, 2018; Mrkajic et al. , 2019; Liu and Liu, 2023; Arsawan et al. , 2023; AlQershi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, self-assessment creates a background for the modelling of future behaviour. Numerous studies have revealed that the relationship between sustainable behaviour motivation and creativity skills is closely related [23]. Personal communication skills help optimise the communication of sustainability.…”
Section: Development Of Creativity Critical Thinking and Communicatio...mentioning
confidence: 99%
“…Indicators of the Kaufman Domains of Creativity Scale (K-DOCS)[23] and assessment of the first-year students of the Faculty of Creativity Industries at Vilnius Gediminas Technical University.…”
mentioning
confidence: 99%